Yangyin Yiqi Mixture Ameliorates Bleomycin-Induced Pulmonary Fibrosis in Rats through Inhibiting TGF-β1/Smad Pathway and Epithelial to Mesenchymal Transition. (3rd January 2019) - Meng, Lihong; Zhang, Xiaomei; Wang, Hong; Dong, Huan; Gu, Xiaofeng; Yu, Xiaolin; Liu, Yushan
Abstract : Objective . The aim of the current study was to investigate the protective effect of Yangyin Yiqi Mixture (YYYQ) on Bleomycin-induced pulmonary fibrosis in rats based on TGF- β 1/Smad signal pathway and epithelial to mesenchymal transition (EMT). Methods . 120 Wistar rats were randomly divided into six groups: control group, BLM group, BLM + Pred group, BLM+YYYQ-L group, BLM+YYYQ-M group, and BLM+YYYQ-H group. Rats were given an intratracheal instillation of 3 mg/kg BLM to establish the pulmonary fibrosis model and followed by different dosages of YYYQ (11, 22, 44g/kg, via intragastric gavage) or prednisone soluble (4.2mg/kg, via intragastric gavage) or water. After 14 days and 28 days, tissue sections were stained with hematoxylin-eosin and Masson's trichrome to observe histopathological changes. Protein levels of TGF- β 1, CTGF, Interleukin 18, and hydroxyproline were detected by ELISA method, and mRNA expressions of TGF- β 1, T β RI, T β RII, Smad3, Smad7, α -SMA, E-cadherin, laminin, and collagen I were detected by RT-PCR. Results . TGF- β 1, CTGF, Interleukin 18, and hydroxyproline levels and mRNA expression of TGF- β 1, T β RI, T β RII, Smad3, α -SMA, laminin, and collagen I were significantly increased ( p <0.01), while Smad7 and E-cadherin levels were significantly decreased in BLM group ( p <0.01). YYYQ-M and YYYQ-H group had downregulated the TGF- β 1, CTGF, hydroxyproline contents, and mRNA expression of TGF- β 1, T β RI, T β RII, Smad3, α -SMA, laminin, and collagen I and upregulated mRNA levels of Smad7 and E-cadherin significantly ( p <0.01 or p <0.05). The result from the present study, which was also supported by histological evidence, suggested that YYYQ-M group and YYYQ-H group exhibited better treatment effect on Bleomycin-induced pulmonary fibrotic rats when compared to that of BLM + Pred group ( p <0.01). Meanwhile, the effect of YYYQ, in three different dosages, on the level of interleukin 18 was not significant. Conclusion . These results showed that YYYQ has the potential of ameliorating the progression of pulmonary fibrosis, and the mechanism may be related to suppressing TGF- β 1/Smad signal pathway and EMT in BLM-induced pulmonary fibrosis of rats.